2013
DOI: 10.4236/ojas.2013.33031
|View full text |Cite
|
Sign up to set email alerts
|

Sugar concentration influences decision making in <i>Apis mellifera</i> L. workers during early-stage honey storage behaviour

Abstract: Decision making in honeybees is based on information which is acquired and processed in order to make choices between two or more alternatives. These choices lead to the expression of optimal behaviour strategies such as floral constancy. Optimal foraging strategies such as floral constancy improve a colony's chances of survival, however to our knowledge, there has been no research on decision making based on optimal storage strategies. Here we show, using diagnostic radioentomology, that decision making in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 53 publications
3
16
1
Order By: Relevance
“…Moreover, clustering of cells with similar concentrations occurred only occasionally, thereby indicating that workers do not follow a consistent rule for spatial nectar storage at this stage of honey production. Our conclusions differ from those of Greco et al (2013) who suggested occurrence of clusters of cells containing similar content in smaller colony units and after a shorter storage period. This shows that honey ripening processes need to be considered under various conditions to provide a more general understanding of the storage behaviour of honeybees.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Moreover, clustering of cells with similar concentrations occurred only occasionally, thereby indicating that workers do not follow a consistent rule for spatial nectar storage at this stage of honey production. Our conclusions differ from those of Greco et al (2013) who suggested occurrence of clusters of cells containing similar content in smaller colony units and after a shorter storage period. This shows that honey ripening processes need to be considered under various conditions to provide a more general understanding of the storage behaviour of honeybees.…”
Section: Discussioncontrasting
confidence: 57%
“…During this time, the hives were kept in a cool room at 14 °C to prevent overheating of the closed compartment. Apart from colony size, hive type and experiment duration, the same experimental and feeding conditions as in Greco et al (2013) were used.…”
Section: Hive Preparation and Feeding Regimementioning
confidence: 99%
See 3 more Smart Citations